(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The characteristics of Imam Saud bin Abdulaziz Royal Reserve are considered a key determinant for sustainable tourism investment and natural resource management. The reserve faces challenges in maintaining its biological diversity due to the lack of scientific studies, which limits the ability to make sound administrative decisions. This research aims to fill this gap using Geographic Information Systems (GIS) and Remote Sensing (RS). The results showed that the predominant soil is Regosols, which are prone to erosion and suitable for light tourism, and that the reserve’s distance from human activities has contributed to the development of biodiversity. Therefore, the study recommends regulating tourism activities to maintain ecological balance